2022
DOI: 10.1093/tbm/ibac074
|View full text |Cite
|
Sign up to set email alerts
|

“It’s hard for everyone” systemic barriers to home confinement to prevent community spread of COVID-19

Abstract: Rapid identification and isolation/quarantine of COVID-19 cases or close contacts, respectively, is a vital tool to support safe, in-person learning. However, safe isolation or quarantine for a young child also necessitates home confinement for at least one adult caregiver, as well as rapid learning material development by the teacher to minimize learning loss. The purpose of this study is to better understand barriers and supports to student home confinement. We conducted a mixed-methods study using focus gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…This is consonant with barriers and hardships faced by other populations during the pandemic [ 20 ], and important in underscoring that parents’ mental health can affect their children’s mental health [ 14 , 21 ]. We have found similar results in other vulnerable populations in the region [ 22 25 ]. With the lifting of public health emergency measures in the United States, social safety net programs will become less accessible to these same populations [ 26 ].…”
Section: Discussionsupporting
confidence: 89%
“…This is consonant with barriers and hardships faced by other populations during the pandemic [ 20 ], and important in underscoring that parents’ mental health can affect their children’s mental health [ 14 , 21 ]. We have found similar results in other vulnerable populations in the region [ 22 25 ]. With the lifting of public health emergency measures in the United States, social safety net programs will become less accessible to these same populations [ 26 ].…”
Section: Discussionsupporting
confidence: 89%
“…Despite the fact that PLWH might be more susceptible to serious complications from COVID-19 and other pandemic-related-HIV-service disruptions [18], and that better understanding the testing access and uptake rates might be key to developing effective testing strategies and improving their overall engagement and wellbeing outcomes, studies addressing access to, utilization of and enablers/barriers to COVID-19 Ag RDT testing are very limited. At the time of writing, only a few related articles considering factors influencing healthcare access during the pandemic [19] and barriers to home isolation as a public health measure to stop the spread of COVID-19 [20] had been published, and these considered different factors than our study. However, there are two studies, from considerably different contexts (England and the USA), which can provide some interesting comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous research that has found stress to be associated with poor mental health (Hammen, 2005 ; Kendler et al, 2000 ; Schneiderman et al, 2005 ). The early phase of the COVID pandemic created a situation of chronic stress for many parents (Omaleki et al, 2022 ). Strategies to reduce individual- and family-level stressors are needed and may be particularly beneficial during the acute phase of public health emergencies (Fong & Iarocci, 2020 ; Omaleki et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The early phase of the COVID pandemic created a situation of chronic stress for many parents (Omaleki et al, 2022 ). Strategies to reduce individual- and family-level stressors are needed and may be particularly beneficial during the acute phase of public health emergencies (Fong & Iarocci, 2020 ; Omaleki et al, 2022 ). Paid family leave, affordable and accessible childcare, and basic universal income should be considered as structural interventions that may reduce stress and improve the health and well-being of families.…”
Section: Discussionmentioning
confidence: 99%